Brown Jaw Tumors: challenges and outcomes - Abdelrahman, Tarek Elsayed Ftohy (International Surgery Journal, 2017)
Background: Brown tumors are very rare giant cell lesions that arise as a result of hyperparathyroidism, brown tumors rarely affect the mandible and maxilla and its diagnosis and treatment is very challenging and needs a high index of suspicion. Methods: Retrospective chart review of nine cases diagnosed as brown jaw tumors treated in maxillofacial, head and neck surgery unit, department of surgery, Sohag University hospital. Results: They were 9 patients, 3 males and 6 females with a mean age of 43.3 years. Lesions were located in the mandible (4 cases), maxilla (3 cases), both mandible and maxilla (2 cases). The main presentation was a mass lesion. Clinical examination and serum parathormone, serum calcium, serum phosphorus, neck ultrasonography, parathyroid scan was used for diagnosis. Cases did excision with parathyroidectomy. There was no recurrence during a mean follow up period of 9.3 months. All patients had satisfactory results. Conclusions: All cases with osteolytic lesions in mandible or maxilla the possibility of brown tumors should be kept in mind especially if there is any manifestation of hyperparathyroidism. This report will aid in the recognition and treatment of the jaw brown tumors.